2020
DOI: 10.1007/s00268-020-05909-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Adrenalectomy for Metastatic Hepatocellular Carcinoma: A 25‐year Institutional Experience

Abstract: Background Extrahepatic manifestation of hepatocellular carcinoma (HCC) is rare and primarily affects lung, lymph nodes and bone. Metastases to the adrenal glands are relatively infrequent. This 25-year institutional experience aimed for an analysis of factors influencing survival in patients undergoing surgery for HCC adrenal metastasis. Methods A retrospective analysis of the institutional database of the Clinic for General-, Visceral- and Transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…[60,61] For the therapy of advanced HCC patients with adrenal glands metastases, surgical resection, ablation, and RT have been reported. [62][63][64] RT is a good palliative therapy for advanced HCC patients with extrahepatic metastases. [65][66][67][68][69] In a multi-institutional retrospective study conducted in Korea, for advanced HCC patients with adrenal metastasis treated with RT, the ORR was 38.3%, disease stability was 93.6%, and the adverse events were minimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[60,61] For the therapy of advanced HCC patients with adrenal glands metastases, surgical resection, ablation, and RT have been reported. [62][63][64] RT is a good palliative therapy for advanced HCC patients with extrahepatic metastases. [65][66][67][68][69] In a multi-institutional retrospective study conducted in Korea, for advanced HCC patients with adrenal metastasis treated with RT, the ORR was 38.3%, disease stability was 93.6%, and the adverse events were minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced HCC with adrenal glands metastatic are not common and the incidence is in the range of 8.8% to 16.9% [60,61] . For the therapy of advanced HCC patients with adrenal glands metastases, surgical resection, ablation, and RT have been reported [62–64] . RT is a good palliative therapy for advanced HCC patients with extrahepatic metastases [65–69] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed conflicting data regarding the laterality of adrenal metastasis. Most studies described predominantly unilateral adrenal [ 13 , 26 , 30 , 31 ], although some studies reported comparable uni- and bilateral involvement [ 32 ] and few studies even reported mostly bilateral metastasis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suprarenal hematoma can be misdiagnosed as metastasis of primary liver cancer, which is a common cause of OLT. It is important to distinguish adrenal hematomas from metastases as they have different clinical outcomes without early intervention [8,9]. Contrast-enhanced ultrasound (CEUS) imaging is highly sensitive to contrast signals in real time, even in the smallest vessels [10].…”
Section: Introductionmentioning
confidence: 99%